The Correlation between Sleep Quality and Level of Stress among Students in Islamic Boarding School Bogor - Bety Semara Lakshmi; Irena Ujianti; Fahrozi Fahrozi; Ibnu Albantani; Ananda Putri; Nofrizal Nofrizal; Agus Rahmadi; Endin Nokik Stujanna; Zahra Nurusshofa; Wawang S Sukarya (Jurnal Kedokteran Brawijaya, 2023)
Sleep period and performance affect mental health. Multiple studies have linked sleep quality and duration to mental health in metabolic patients, but studies on sleep patterns and mental health symptoms in healthy people, especially in Islamic boarding schools, are limited. The goal of this research is to look into the relationship between sleep patterns and performance in relation to mental health in students who attend Islamic boarding schools. In this cross-sectional study, a self-administered questionnaire consisting of the Pittsburgh Sleep Quality Index (PSQI) and the Depression, Anxiety, and Stress Scale-21 (DASS21) was distributed to students at the Wadi Mubarok Islamic boarding school. Total blood sugar and cholesterol levels were measured using EasyTouch glucometer. Fasting glucose levels are used to support the results of stress conditions in the body, which are indicated by an increase in fasting blood glucose levels, which are normally less than 100mg/dl. To see the relationship, a Spearman rank correlation test was carried out. From the results of the examination, plasma glucose levels were 118.1±4.03mg/dl, and plasma uric acid levels were 5.54±0.24 mg/dl. There is a weak correlation between sleep quality and depression (r=0.341; p<0.05) and a fairly strong correlation between sleep quality and anxiety (r=0.437; p<0.05). In this study, poor sleep quality and short sleep duration were linked to an increased incidence of depression and anxiety symptoms. These findings imply that inadequate sleep duration and performance could be a contributor to the development of mental disorders.